Manajemen Kepemimpinan Partisipatif Kepala Madrasah Sebagai Strategi Penguatan Mutu Pendidikan Di MTs Mathalibul Huda Mlonggo - Budiyanto, Budiyanto; Sukarman, Sukarman; Setianto, Rully; Fitria, Nurul (Universitas Pakuan, 2026)
PARTICIPATORY LEADERSHIP MANAGEMENT OF THE MADRASAH PRINCIPAL AS A STRATEGIC APPROACH TO STRENGTHENING EDUCATIONAL QUALITY AT MTS MATHALIBUL HUDA MLONGGOImproving the quality of education at the Madrasah Tsanawiyah (MTs) level has become a strategic urgency amid increasing demands for accountability, curriculum dynamics, and the need to strengthen teacher professionalism. Many educational institutions continue to face challenges such as disparities in competence, weak collaborative culture, and imbalanced roles in decision-making processes. In this context, MTs Mathalibul Huda Mlonggo demonstrates unique characteristics, including a strong culture of deliberation (musyawarah), collective participation, and open communication among the principal, teachers, and stakeholders. These conditions position the madrasah as an intriguing case for an in-depth examination of participative leadership practices. This study aims to analyze how participative leadership management is formulated, implemented, and contributes to improving educational quality. Employing a qualitative approach with a case study design, data were collected through interviews, observations, and document analysis, and were subsequently analyzed using an interactive model. The findings indicate that teacher involvement in decision-making, dialogic supervision systems, a collaborative culture, and participation-based planning effectively enhance instructional quality, program consistency, and governance accountability. The study concludes that participative leadership serves as an effective strategy for madrasahs to sustainably improve educational quality and may be replicated by other institutions with similar characteristics.